2017
DOI: 10.1016/j.jafrearsci.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of a mountain: The Thebes Limestone Formation (Lower Eocene) at Gebel Gurnah, Luxor, Nile Valley, Upper Egypt

Abstract: 32We present a detailed geologic study of the Thebes Formation at Gebel Gurnah in its locus 56Key words: Thebes Limestone, Lower Eocene, Gebel Gurnah, Egypt, sequence stratigraphy. 58 59 I-Introduction 61The Lower Eocene* Thebes Formation is one of the thickest (~340 m) and regionally extensive 62 outcropping lithostratigraphic units of Egypt (Snavely et al., 1979; Fig. 1). Extending from the 63Farafra Oasis in the west to Upper Egypt (mostly between Qena-Esna) and beyond to the Red 64Sea coast and the Sinai … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…For this paper, we will use the same stratigraphic column (Figure 3B) that we presented in Tewksbury et al (2017a), which uses the Thebes Group nomenclature. Figure 3B also shows our best estimate for stratigraphic thicknesses under our study area based on recent work by King et al (2017), combined with data from the Assiut-Kharga well. Detailed rationale for both the stratigraphic (1981).…”
Section: Background and Prior Work Geologic Settingmentioning
confidence: 89%
See 2 more Smart Citations
“…For this paper, we will use the same stratigraphic column (Figure 3B) that we presented in Tewksbury et al (2017a), which uses the Thebes Group nomenclature. Figure 3B also shows our best estimate for stratigraphic thicknesses under our study area based on recent work by King et al (2017), combined with data from the Assiut-Kharga well. Detailed rationale for both the stratigraphic (1981).…”
Section: Background and Prior Work Geologic Settingmentioning
confidence: 89%
“…Depths to specific formations are based primarily on Assiut-Kharga well (Barakat and Asaad, 1965), located in the middle of our study area. Data from El-Azabi and Farouk (2011), King et al (2017), Said (1960, 1962, 1990), El Hinnawi et al (1978, Issawi (1972), Issawi et al (2009), , Khalil and El-Younsy (2003), El Hinnawi et al (2005). Reprinted from Tewksbury et al (2017a) with permission from Elsevier.…”
Section: Background and Prior Work Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancient Egyptians constructed houses, palaces, temples and tombs mainly of environmental stones (Falana et al, 2020) and limestone and sandstone was the most commonly used materials in the construction of sacred buildings in Egypt because of its resistant to harsh weather. During the period of Queen Hatshepsut, Hatshepsut temple was built of local materials from Thebes limestone extracted from ancient quarry in Gebel Qurna (Aubry et al, 2009), (Pawlicki, 2017) (King, 2017). The study of Graue et al, (2007) revealed that severe deterioration results into the structural disintegration of rock masses, which is as a result of a clearly pronounced cataclastic overprint and has become a major structural problem since the tomb's origin.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the hill above the KV62 tomb is constituted both by limestone of the Thebes formation and by natural aerated debris from the valley sides. Further details on the geology and on the properties of the materials could be found for example in Wust and McLane, 2000;Aubry et al, 2009, Dupuis at al., 2011, King et al, 2017 and other references cited therein. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%